Digital Marketing Media Development at Nutrihub Lampung - Permana, Yoga; Realita, Reza; Ariani, Rizki Okti; Purbasari, Niken; Pujian S, Andreas; Bangun, Sanjaya; Fihartini, Yuniarti (CV. Tripe Konsultan, 2023)
This community service is related to digitizing transformation in co-working spaces where the output is in the form of a prototype landing page design for UMKM Nutrihub Lampung. Nutrihub Lampung is a co-working space that is a new concept of a place to work for independent workers. In this service activity, the stages of making landing pages, landing page designs, and the implementation process are explained. The service was carried out at Nutrihub Lampung by collecting data through observation and Focus Group Discussion. The data is processed through analysis, design, implementation and drawing conclusions. The results of this service are expected to increase interaction with the community on a wider scope and are expected to increase additional turnover for business owners. Easy access to flexible and dynamic work support facilities/facilities and semi-formal, communal, and collaborative work environments are the main attraction for co-working space users. The shift to technology-based jobs is increasing the demand for affordable, flexible and dynamic workplaces.